Closing wedge distal femoral osteotomy for knee valgus: indications, technique, rehabilitation and outcomes - Jae-Sung An; Kristian Kley; Christophe Jacquet; Levi Reina Fernandes; Matthieu Ollivier (Elsevier, 2023)
Introduction: In cases of symptomatic knee valgum, in which deformity majorly originated in the femoral distal metaphysis, 2 main types of femoral osteotomy have been described: medial closing or lateral opening. We have been doing medial closing wedges with anterior second plane cut for years. The reason being a proven similar surgical accuracy associated to a higher and faster healing rate promoted by a larger contact area between the 2 sides of the osteotomy site. The aim of this article is to describe up-to-date closing wedge distal femoral osteotomy strategies: from indication, to ideal correction, surgical technique and patient recovery. Methods: Distal femoral varus osteotomy is indicated in painful valgus knee in which deformity originated majorly in the femoral distal metaphysis. The planning is digitally performed according to the Miniaci method using digital software to have a postoperative weight bearing line passing through the knee joint at 45% to 50% measured from the medial tibial plateau border (0%) to the lateral tibial plateau border (100%). The procedure is performed through medial closing wedges created with 2 medial to lateral and 1 posterior to anterior cutting planes creating an anterior biplanar cut. Results: Using our step-by-step way to perform closing wedge distal femoral osteotomy, we standardized our radiological and clinical outcomes. Knowing some tips and tricks to avoid intraoperative complications will help readers to master this procedure. Conclusions: Following simple intraoperative landmark and technical guidance bony deformity can be fully corrected by medial closing wedges using an anterior biplanar cut. Patients will demonstrate optimal clinical outcomes including high rate of return to recreational and professional activities.